Immunomodulation in Primary Immune Thrombocytopenia: A Possible Role of the Fc Fragment of Romiplostim? - Schifferli, Alexandra; Nimmerjahn, Falk; Kühne, Thomas (Frontiers in Immunology, 2019)
Fc fusion proteins and Fc fusion peptides or peptibodies are chimeric molecules composed of an active pharmacological protein or peptide and the Fc fragment of an immunoglobulin. The primary aim of this drug construct is to prolong the half-life of the active component. This molecular architecture is seen in drugs, such as etanercept, romiplostim and the recombinant factor VIII (efmoroctocog alfa). A considerable number of Fc fusion proteins and peptibodies are currently in preclinical and clinical development. The isolated effect of the Fc fragment has been studied intensively during last years, but is still poorly understood in the clinical setting and in relation with the active drug and underlying disease. In this short review, we will propose new hypotheses of possible immunomodulatory functions of the Fc fragment of romiplostim in patients with primary immune thrombocytopenia.